Украина в трансформационных процессах: Quo vadis? - Куценко, О. (Социология: теория, методы, маркетинг, 2007)
The analysis of the major societal trends and outcomes of Ukrainian post-Socialist development is provided in the article. The author's focus is directed towards revealing of interconnection between the market shifts, changes of social mood, consciousness and structure, institutional quality and political accountability. The social dynamics during the post-Socialist epoch, from reversing displacement in social and political institutional matter at the end of 1990s towards explosion of social expectations at the line of 2004-2005 and the following mass disappointment which accompanies the increasing contemporary political deregulation is considered from the point of view of search for answers regarding the perspective features of Ukrainian development.